Analysis of The Effectiveness of Casting Machine Using OEE Method and 5 Whys Analysis - Rydhoni, Rydhoni; Aribowo, Budi; Nurhasanah, Nunung (Universitas Al Azhar Indonesia, 2024)
Casting machine is a production tool with the function of molding liquid aluminum into velq products used at PT XYZ. In carrying out the production process, casting machines often experience failures that affect the high machine downtime and also the ineffective use of machines to run the production process. The purpose of this research is to implement Total Productive Maintenance by analyzing the use of machines with the OEE method to determine the value of their effectiveness and conducting breakdown analysis using the 5 why's analysis method to find the root of the problem that affects the calculation of the OEE value of the machine so that a solution can be formulated to overcome these problems. Based on OEE calculations on the casting machine for the January-June 2022 period, the performance rate measurements in January and May were 89. 19% and 83.28% which were below the Nakajima standard. The results of the May performance rate calculation have an impact on the OEE value which does not reach the standard of 82.17%. By using 5 Why's analysis, the cause of the low performance rate value in both months is the operator who makes changes to the machine settings so that the actual cycle time of machine operation is higher than before and causes reduced speed losses.Keywords - Casting machine, OEE, performance rate, 5 why’s analysis, reduce speed losses